Examining bribery in Papua New Guinea's public sector: forms and accountability implications. Issue 1 (22nd October 2020) - Tiki, Samson; Luke, Belinda; Mack, Janet
Abstract : Purpose: The purpose of this study is to examine bribery and its accountability implications within Papua New Guinea's (PNG's) public sector. Design/methodology/approach: Semi-structured interviews were conducted with 11 senior public servants from three central government departments. Perceptions, forms and accountability dimensions compromised through bribery were analysed through an actor network theory (ANT) lens to understand the actors contributing to bribery and how it might be addressed. Findings: Forms (and variations) of bribery included "promises" by clients, pre-commitments by public servants and expectations/obligations imposed by public servants. Multiple and interdependent actors (including compromised accountability perceptions) are identified. Practical implications: Findings provide important insights for public servants and policy-makers within and beyond PNG's government departments, highlighting the associated implications for individuals, the public sector and the country more broadly. Originality/value: The incorporation and analysis of accountability dimensions through an ANT lens provides new perspectives on bribery. Further, the significance and extent of compromised accountability dimensions within the network suggests a broken accountability system.